The role of mass media in the formation of civil identity (with reference to the Russian Federation and the Republic of Kazakhstan) - Tkhabisimova, L.A.; Bilyalova, M.I.; Musilimova, K.S. (Bulletin of the Karaganda University “Law Series”, 2025)
The article explores the role of the education system, mass media, and Internet resources in shaping personality in the digital age. The authors argue that, although education remains important, it cannot fully compete with the powerful influence of mass media and the Internet on the formation of social identity. Particular attention is given to how television, online platforms, and social media have become key tools in shaping both public and individual consciousness. Even those who try to avoid media influence inevitably become a part of the constant information flow of daily life. The media now play a dominant role in forming social identity, especially amid rapid technological development and broad access to information. With the rise of the Internet, individuals have become not only consumers but also content creators, blurring the line between professional journalism and user-generated content. This shift has created new forms of communication that influence the perception of social values and shape civic identity. Media platforms serve not only as sources of information but also as arenas for discussing political, cultural, and social issues, thereby impacting collective consciousness and national identity.